Emphysematous pyelonephritis in failed renal allograft:Case report and review of literature - Rahul Kumar Bansal; Shahid Lambe; Anil Kapoor (Urology Annals, 2016)
Emphysematous pyelonephritis (EPN) in renal allograft is rare but potentially lethal complication and requires aggressive medical and/or surgical therapy to achieve cure. We report a case of 60-year-old diabetic male with poor cardiac function on maintenance hemodialysis, who underwent delayed allograft nephrectomy for EPN in failed renal allograft. Blood culture grew Bacteroides. He was stable in the postoperative period but passed away on day 4 due to myocardial infarction likely secondary to poor baseline cardiac function. Delay in diagnosis and treatment could have contributed to this unfavorable outcome. There is a paucity of published literature regarding EPN in the transplant population, such that management decisions (percutaneous conservative versus urgent surgical) are challenging. Further studies are required to establish treatment guidelines.